Nursing mentoring and mentors' views on the efficiency of university students' practice - Govekar-Okoliš, Monika (AS. Andragoška spoznanja, 2020)
The article describes the views nurse mentors have on the efficiency of their mentoring of nursing students in one of the public hospitals in Slovenia. This is one of the least addressed fields of research, particularly when evaluating the effects of nurse mentors. The purpose of the quantitative study is to ascertain the situation and effects nurses have when mentoring university students during their clinical practice. The descriptive method of empirical research was applied. The research was based on the analysis of a questionnaire for nurse mentors. The goal was to find out how they view mentorship efficiency, how to increase it, and how mentors evaluate their competences, difficulties, etc. The study's findings bring new insights and important recommendations on how to improve mentoring during the clinical practice of nursing students. The research showed that mentors needed pedagogical and andragogical knowledge. The results are important for improving the quality of nursing mentorship and positively affect their further education and professional development. It would also be important to establish a Slovenian, European and international network of nursing mentorship for university students in the future. This would have an impact on the international cooperation of nurse mentors and their mentoring efficiency, as well as better practical training and employment for students of nursing.
Keywords: clinical practice; klinična praksa; mentorji študentom; mentorstvo; mentorstvo medicinskih sester; nurse mentors; nursing mentorship; študentska praksa; university students; univerzitetni študij